The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/bcp.13848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampin on enantioselective disposition and anti‐hypertensive effect of benidipine

Abstract: AIMSIn vitro study showed that benidipine is exclusively metabolized by cytochrome P450 (CYP) 3A. This study evaluated the effect of rifampin on the enantioselective disposition and anti-hypertensive effect of benidipine. METHODSBenidipine (8 mg) was administered to healthy subjects with or without repeated rifampin dosing, in a crossover design. Plasma concentrations of (S)-(S)-(+)-α and (R)-(R)-(À)-α isomers of benidipine and blood pressure were measured for up to 24 h after dosing. In addition, CYP3A metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…It is the most influential enzyme inducer of hepatic cytochrome P450 enzymes that lead to increased metabolism of many drugs and turns them into ineffective drugs such as warfarin, birth control pills, antiretrovirals, immune suppressants, as well as some anti-hypertensives such as calcium channel blockers, beta-blockers, and diuretics [7]. Several studies have reported that rifampicin has potentially diminished the hypotensive effects of many anti-hypertensive agents by inducing cytochrome P450 [8][9][10]. Thus, this study aims to investigate the effect of rifampicin on the target blood pressure in known hypertensives whose blood pressure had been previously controlled with anti-hypertensives.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most influential enzyme inducer of hepatic cytochrome P450 enzymes that lead to increased metabolism of many drugs and turns them into ineffective drugs such as warfarin, birth control pills, antiretrovirals, immune suppressants, as well as some anti-hypertensives such as calcium channel blockers, beta-blockers, and diuretics [7]. Several studies have reported that rifampicin has potentially diminished the hypotensive effects of many anti-hypertensive agents by inducing cytochrome P450 [8][9][10]. Thus, this study aims to investigate the effect of rifampicin on the target blood pressure in known hypertensives whose blood pressure had been previously controlled with anti-hypertensives.…”
Section: Introductionmentioning
confidence: 99%